1979
DOI: 10.1111/j.1476-5381.1979.tb08681.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cerebral 5‐hydroxytryptamine on Catalepsy Induced by Brain‐amine Depleting Neuroleptics or by Cholinomimetics

Abstract: 1 Catalepsy was produced in rats and mice by the subcutaneous injection of either tetrabenazine or the butyrophenone U-32,802A (4'-fluoro-4-{[4-(p-fluorophenyl)3-cyclohexen-1-yl]aminoI butyrophenone hydrochloride). Catalepsy was evaluated by the duration of total immobility on a vertical grid.2 Pretreatment with p-chlorophenylalanine (PCPA) reduced the intensity of catalepsy by 50% or more, whereas its time course remained the same. 3 5-Hydroxytryptophan (5-HTP), 10 mg/kg, enhanced the catalepsy induced by U-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Previous reports have indicated that impairment of the 5-HT-ergic system attenuated the intensity of neuroleptic induced catalepsy (Costall et al, 1975;Fuenmayor & Vogt, 1979). However, in the work reported here, the depletion of 5-HT produced by preadministration of the tryptophan-5-hydroxylase inhibitor, PCPA, did not affect the cataleptogenic activity of a-FPT.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previous reports have indicated that impairment of the 5-HT-ergic system attenuated the intensity of neuroleptic induced catalepsy (Costall et al, 1975;Fuenmayor & Vogt, 1979). However, in the work reported here, the depletion of 5-HT produced by preadministration of the tryptophan-5-hydroxylase inhibitor, PCPA, did not affect the cataleptogenic activity of a-FPT.…”
Section: Discussioncontrasting
confidence: 54%
“…In view of the reported modulation of neurolepticinduced catalepsy by 5-HT (Costall, Fortune, Naylor, Marsden & Pycock, 1975;Fuenmayor & Vogt, 1979) the current investigation was performed to evaluate whether procedures affecting 5-HT-ergic 0007-1 188/83/010137-06-$01.00 systems in any way modified the ability of GABAergic drugs to potentiate neuroleptic-induced catalepsy.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate an important role for 5-HT in the regulation of the cataleptic effect of molindone and suggest that the activation of the central 5-HT-ergic system has a facilitatory effect on the catalepsy induced by molindone while inhibition of the central 5-HT-ergic system decreases the cataleptic effect of molindone. Further, our results also indicate that the central 5-HT-ergic system influences molindone-induced catalepsy in the same manner as it influences haloperidol or chlorpromazineinduced catalepsy (Kostowski et a1 1972;Gumulka et a1 1973;Carter & Pycock 1977;Balsara et a1 1979) or catalepsy induced by brain-amine depleting neuroleptics (Fuenmayor & Vogt 1979) and suggest that the central 5-HT-ergic system may be exerting an inhibitory influence on the central dopaminergic system and that the cataleptic effect of neurileptics gpparently depends on the balance between the two systems. These findingsalso concur with clinical reports.…”
mentioning
confidence: 71%
“…Of note, several studies reported a beneficial effect of 5-HT 1A agonists in reversing and preventing the development of catalepsy in rodents [83,84], suggesting that the combination of a 5-HT 1A agonist and a D 2 antagonist may lead to antipsychotic activity free of extrapyramidal symptoms [82]. Other animal studies have confirmed a role for 5-HT 2 receptors in alleviating catalepsy through the use of specific 5-HT 2A antagonists [85,86] and have also shown that 5-HT 2 antagonists enhance dopamine-mediated motor behaviour in models other than catalepsy [87,88]. Though Kapur and Seeman [89] have recently argued in their PET studies that the occupancy of 5-HT 2A is not a necessary condition for atypicality, PET occupancy metrics may not be directly correlated to drugs’ antipsychotic mechanism of action.…”
Section: The Dopamine-serotonin System and Taar1 Receptor In The Pmentioning
confidence: 99%